Why Don't Banks Lend to Egypt's Private Sector? - Herrera, Santiago; Hurlin, Christophe; Zaki, Chahir (Elsevier, 2013)
Bank credit to Egypt's private sector decreased over the last decade, despite a recapitalized banking system and high rates of economic growth. Recent macro-economic turmoil has reinforced the trend. This paper explains the decrease based on credit supply and demand considerations by 1) presenting stylized facts regarding the evolution of the banks' sources and fund use in 2005 to 2011, noting two different cycles of external capital flows, and 2) estimating private credit supply and demand equations using quarterly data from 1998 to 2011. The system of simultaneous equations is estimated both assuming continuous market clearing and allowing for transitory price rigidity entailing market disequilibrium. The main results are robust to the market clearing assumption. During the global financial crisis, a significant capital outflow stalled bank deposit growth, which in turn affected the private sector's credit supply. At the same time, the banking sector increased credit to the government. Both factors reduced the private sector's credit supply during the period under study. After the trough of the global crisis, capital flowed back into Egypt and deposit growth stopped being a drag on the supply side, but bank credit to the government continued to drive the decrease in the private sector's credit supply. Beginning in the final quarter of 2010, capital flows reversed in tandem with global capital markets, and in January 2011 the popular uprising that ousted President Hosni Mubarak added an Egypt-specific shock that accentuated the outflow. Lending capacity dragged again, accounting for 10% of the estimated fall in private credit. Credit to the government continued to drain resources, accounting for 70–80% of the estimated total decline. Reduced economic activity contributed around 15% of the total fall in credit. The relative importance of these factors contrasts with that of the preceding capital inflow period, when credit to the government accounted for 54% of the estimated fall, while demand factors accounted for a similar percentage.